Long-term couple relationships - stress, problems and coping processes in couple counseling: Insights based on five case studies with five long-term couples - Kieslich, Ute; Steins, Gisela (Frontiers in Psychology, 2022)
In the course of demographic change, the proportion of older people in many countries is rising continuously and more and more people are experiencing a long time together as a couple. In old age, subjective wellbeing and health aspects are associated with partners’ satisfaction with couple relationship. The need for couple counseling in old age is growing in parallel with demographic developments. However, empirical studies on couple therapy with older people in long-term couple relationships exist to date only to a limited extent. The present contribution deals with this knowledge gap. In an explanative two phases design, research has been conducted with long-term couples in couple counseling of which we would like to present here the central qualitative study. The aim is to be able to describe details of these factors. Older couples who have lived in long-term couple relationships were interviewed after using standardized questionnaires concerning the individual and couple-related stress factors and problems at the beginning (N = 62) and the end (N = 36) of their couple counseling process. Five couples from this study were the interviewees for the following study. The couples were interviewed separately. In this interview study and central part of this contribution, the stress factors, problem areas and coping processes of the older couples were examined. The results serve as a suggestion for further research and can only be interpreted with caution due to the small sample of five case studies: The central results of the study are summarized in a circular process model and are discussed in the light of relevant theoretical approaches. The culmination of massive chronic and acute strains and losses associated with feelings of excessive demands and desperation gave rise to emotional alienation of the partners. In the course of couple therapy, the partners mutually opened their thoughts and emotions and modified their previous dysfunctional pattern of interaction. Thus, emotional and physical rapprochement of the partners was fostered with the effect that subjective load of the partners and dissatisfaction of the couple relationship decreased, and subjective emotional wellbeing increased. To prevent negative emotions and destructive conflicts with their spouse, some of the interviewed partners actively used avoidance strategies in couple interactions. Upon completion of couple therapy changes in the couple relationships appeared instable as soon as overcharging stress factors occurred again. The results suggest that an approach to couple therapy for older people in long-term couple relationships should prioritize emotional safeness and attachment in couple relationship to facilitate constructive conflict management. The couple therapy process should emphasize emotion regulation strategies based on age-related strengths and consider age-related vulnerabilities. Moreover, long-term couples may benefit from catamnestic consultation appointments to consolidate the developed changes.